2014
DOI: 10.1155/2014/475389
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Secondary Structure and Surface Hydrophobicity of Soybean Protein Isolate Subjected to Heat Treatment

Abstract: This study investigated relationship between secondary structure and surface hydrophobicity of soy protein isolate (SPI) subjected to a thermal treatment at 70~90°C. Heat denaturation increased the surface hydrophobicity and surface hydrophobicity decreased as aggregate formed. Heat caused an increase in the relative amount ofα-helix structures and an overall decrease in the amount ofβ-sheet structures when compared with nontreated SPI. The relative amounts of secondary structures varied with time, temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
109
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 192 publications
(124 citation statements)
references
References 42 publications
12
109
2
1
Order By: Relevance
“…Consistent with the results of our study, our previous research also showed that protein aggregate have higher β-sheet and β-turn content. [36] The α-helix content of MBPI-D-90 gradually increased and then decreased with treatment time, while the β-sheet content first decreased and then increased. The change in these structures of MBPI-D-90 was similar to that observed in MBPI-D-80.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Consistent with the results of our study, our previous research also showed that protein aggregate have higher β-sheet and β-turn content. [36] The α-helix content of MBPI-D-90 gradually increased and then decreased with treatment time, while the β-sheet content first decreased and then increased. The change in these structures of MBPI-D-90 was similar to that observed in MBPI-D-80.…”
Section: Discussionmentioning
confidence: 95%
“…We previously showed that protein denaturation increases the surface hydrophobicity, and that surface hydrophobicity decreases as aggregates are formed. [36] In general, the surface hydrophobicity of MBPI-D-90 was lower than that of MBPI-D-80, which suggested that more dextran grafting and aggregation formation decreased protein hydrophobicity to a large extent. …”
Section: Emulsifying Propertiesmentioning
confidence: 90%
“…It has been suggested before that heating whilst grinding aqueous soy slurry causes proteinaceous material to aggregate due to denaturation (Nishinari et al, 2014). Thermal denaturation of the main storage proteins b-conglycinin and glycinin occurs in the ranges 74-77°C and 92-93.7°C respectively, which accounts for aggregation when soybeans were ground at 80°C (Kinsella, 1979;Wang et al, 2014). Aggregation of supernatant protein of a size less than 40 nm occurs upon heating of soymilk to increase the concentration of protein particles in the size range 40-110 nm (Ono et al, 1991).…”
Section: Resultsmentioning
confidence: 99%
“…Nonheat treated protein extraction was also carried out at ambient temperature as a control. After a total of 30 min grinding, the soy slurry increased to 41.4°C as no temperature control was performed, which is well below the denaturation temperatures for the main storage proteins, b-conglycinin and glycinin (74-77°C and 92-93.7°C, respectively; Kinsella, 1979;Wang et al, 2014).…”
Section: Sample Preparationmentioning
confidence: 99%
“…Moreover, defining and measuring protein functionality start at the level of protein structure (Wang, Li, Jiang, Qi & Zhou, 2014).…”
Section: Thermal and Xrd Propertiesmentioning
confidence: 99%